2020
DOI: 10.1128/cmr.00006-19
|View full text |Cite
|
Sign up to set email alerts
|

Human Melioidosis

Abstract: SUMMARY The causative agent of melioidosis, Burkholderia pseudomallei, a tier 1 select agent, is endemic in Southeast Asia and northern Australia, with increased incidence associated with high levels of rainfall. Increasing reports of this condition have occurred worldwide, with estimates of up to 165,000 cases and 89,000 deaths per year. The ecological niche of the organism has yet to be clearly defined, although the organism is associated with soil and water. The culture of appropriate clinical material rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
237
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(249 citation statements)
references
References 585 publications
(1,029 reference statements)
8
237
1
3
Order By: Relevance
“…The overwhelming majority of patients with cardiac involvement were males (95.1%). Although this is consistent with the male predominance worldwide, this is a higher percentage when compared to figures of 58.5% in Thailand to 84% in Singapore [ 53 ]. This study identified that the majority of patients were farmers, military personnel, agriculturists, construction or shipyard workers, so this may be due to males receiving disproportionately more occupational exposure to contaminated soil and water.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The overwhelming majority of patients with cardiac involvement were males (95.1%). Although this is consistent with the male predominance worldwide, this is a higher percentage when compared to figures of 58.5% in Thailand to 84% in Singapore [ 53 ]. This study identified that the majority of patients were farmers, military personnel, agriculturists, construction or shipyard workers, so this may be due to males receiving disproportionately more occupational exposure to contaminated soil and water.…”
Section: Discussionsupporting
confidence: 84%
“…There were 49 patients with pericardial involvement reported in the literature [ 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 50 , 51 , 52 , 53 ], with sufficient information for study inclusion obtained to include 32 patients (78.0%) [ 10 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 50 , 51 , 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…While chronic melioidosis is also a clinically relevant form of the disease, the work described here focused exclusively on developing an acute model. In context of human disease, acute melioiodis is the majority of reported cases (estimated to be greater than 80% of human cases) and results from recent exposure to bacteria [ 2 , 43 ]. Characteristics associated with acute melioidosis include bacteremic pneumonia (depending on the route of infection may be primary or secondary pneumonia) and systemic inflammatory and immune responses observed in multiple organ systems.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics associated with acute melioidosis include bacteremic pneumonia (depending on the route of infection may be primary or secondary pneumonia) and systemic inflammatory and immune responses observed in multiple organ systems. The formation of large granulomas in various organs is also considered a hallmark of melioidosis disease [ 2 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chloroxine is soluble to 644 μM in water, and the peak ceftazidime concentration in serum is 130 μM [55]. Furthermore, B. pseudomallei invades and multiplies in phagocytic cells [56], so modification for penetration of these cells would be necessary. A wider range of starting lead scaffolds would likely be necessary for such optimization.…”
Section: Plos Onementioning
confidence: 99%